2001
DOI: 10.1016/s1097-2765(01)00256-8
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Atypical Protein Kinase Domain of a TRP Channel with Phosphotransferase Activity

Abstract: Transient receptor potential (TRP) channels modulate calcium levels in eukaryotic cells in response to external signals. A novel transient receptor potential channel has the ability to phosphorylate itself and other proteins on serine and threonine residues. The catalytic domain of this channel kinase has no detectable sequence similarity to classical eukaryotic protein kinases and is essential for channel function. The structure of the kinase domain, reported here, reveals unexpected similarity to eukaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
268
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(277 citation statements)
references
References 42 publications
9
268
0
Order By: Relevance
“…Additional characterizations of these mutants demonstrate the loss of MgATP and MgGTP block in the phosphotransferase-deficient mutant K1648R. The lysine residue mutated is implicated in nucleotide binding and catalysis and is conserved in classical kinases (Yamaguchi et al 2001). In the second mutant, G1799D, a site that might coordinate the Mg-phosphate complex, some regulation remains, even though phosphotransferase activity is lost.…”
Section: Regulation By Free Mg 2+ and Mg·atpmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional characterizations of these mutants demonstrate the loss of MgATP and MgGTP block in the phosphotransferase-deficient mutant K1648R. The lysine residue mutated is implicated in nucleotide binding and catalysis and is conserved in classical kinases (Yamaguchi et al 2001). In the second mutant, G1799D, a site that might coordinate the Mg-phosphate complex, some regulation remains, even though phosphotransferase activity is lost.…”
Section: Regulation By Free Mg 2+ and Mg·atpmentioning
confidence: 97%
“…Clapham and colleagues (Runnels et al 2001) suggested that the kinase domain is absolutely required for channel activation based on the effects of ATP and the absence of TRPM7 currents in two mouse TRPM7 mutants that were designed to inactivate phosphotransferase activity [G1796D and the double mutant C1809A/C1812A; although based on structural considerations, the latter mutant may not represent a phosphotransferase-deficient construct (Yamaguchi et al 2001)]. This interpretation is probably incorrect, since the ATP effect is attributable to Mg 2+ chelation and the lack of TRPM7 currents when expressing the mutant channels was likely due to failed expression of TRPM7 mutant proteins, since studies from two other laboratories have demonstrated that mutated human TRPM7 channels without phosphotransferase activity still exhibit channel activation comparable to wildtype TRPM7 (Schmitz et al 2003;Matsushita et al 2005).…”
Section: Regulation By the Endogenous Kinase Domainmentioning
confidence: 99%
“…Moreover, three members of the TRPM family, i.e., TRPM2, TRPM6 and TRPM7, differ from other ion channels because they harbor enzyme domains in their C-termini and represent prototypes of a new protein family of enzyme-coupled ion channels. Thus, the NUDT9 domain in TRPM2 was shown to have ADP-ribose pyrophosphatase activity , while the C-termini of TRPM7 and TRPM6 contain a serine/threonine protein kinase domain resembling that of elongation factor 2 (eEF-2) kinase and other α-kinases (Chubanov et al 2004;Drennan and Ryazanov 2004;Nadler et al 2001;Riazanova et al 2001;Runnels et al 2001Runnels et al , 2002Schlingmann et al 2002;Walder et al 2002;Yamaguchi et al 2001). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Several additional catalytic domains related to EF2K and MHCK have been identified through data base searches in mammals as well as in nematode worm, although the function of these potential protein kinases is not known (1)(2)(3). Using this approach, we and others identified an 1863-amino acid polypeptide (termed ChaK for channel kinase) that contained a TRP-related channel domain fused to the atypical kinase domain at its C terminus (3,4). The same gene product was also identified in a yeast two-hybrid screen using a portion of phospholipase C ␤1 as bait (and termed TRP-PLIK) (5) and in a screen for TRP-related channels (and termed LTRPC7) (6).…”
mentioning
confidence: 99%
“…1A). We have recently determined the crystal structure of the kinase domain of TRPM7 (4). The TRPM7 kinase domain (residues 1551-1577) forms a domain-swapped bilobate dimer.…”
mentioning
confidence: 99%